2001
DOI: 10.1046/j.1365-2222.2001.01152.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of C–C chemokine TARC in human nasal mucosa and its regulation by cytokines

Abstract: These results demonstrate a crucial role of nasal epithelial cells in the expression of TARC, and that Th2 cytokine IL-4 and IL-13 may promote Th2 responses by inducing TARC production from epithelial cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 29 publications
(29 reference statements)
2
64
0
1
Order By: Relevance
“…This swift induction appears to be typical, as similar kinetics are seen with many IL-4-induced genes including SOCS-1 [29,38], FIZZ1 [39], Eotaxin/CCL11 [28] and Eotaxin-3/CCL26 [27]. Most other cell types that were examined for IL-4 inducibility of TARC/CCL17 require simultaneous stimulation with TNF-a to up-regulate its expression [8,21,30,33,[40][41][42]. Such cooperative effects of IL-4 and TNF-a stimulation were shown before for other genes.…”
Section: Ccl17 In T Cells and To Characterize The Regulatory Promotermentioning
confidence: 77%
See 2 more Smart Citations
“…This swift induction appears to be typical, as similar kinetics are seen with many IL-4-induced genes including SOCS-1 [29,38], FIZZ1 [39], Eotaxin/CCL11 [28] and Eotaxin-3/CCL26 [27]. Most other cell types that were examined for IL-4 inducibility of TARC/CCL17 require simultaneous stimulation with TNF-a to up-regulate its expression [8,21,30,33,[40][41][42]. Such cooperative effects of IL-4 and TNF-a stimulation were shown before for other genes.…”
Section: Ccl17 In T Cells and To Characterize The Regulatory Promotermentioning
confidence: 77%
“…Hence, the present work was intended to study the IL-4 inducibility of the expression of TARC/ [27]. Most other cell types that were examined for IL-4 inducibility of TARC/CCL17 require simultaneous stimulation with TNF-a to up-regulate its expression [8,21,30,33,[40][41][42]. Such cooperative effects of IL-4 and TNF-a stimulation were shown before for other genes.…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…Airway epithelial cells induce migration of Th1 cells into mucosae via production of the CXCR3 ligands, CXCL9 (Mig), CXCL10 (IP-10) and CXCL11 (I-TAC), and induce migration of Th2 cells via production of the CCR8 ligand CCL1 (I-309) and the CCR4 ligands CCL17 (TARC) and CCL22 (MDC) (Figure 1) [42][43][44][45][46][47]. CXCR3 is expressed on activated T cells, predominantly of the Th1 phenotype, as well as on NK cells and a subset of circulating memory CD4 + and CD8 + T cells.…”
Section: Interaction Of Epithelial Cells With T Cellsmentioning
confidence: 99%
“…Thus, the expressions of IL-4, CCR4, and CCR8 may require allergen stimulation in the inflamed region. In addition, TARC and MDC are expressed not only in airway epithelium but also in the other organs such as skin (31,32) and the nose (33). Taken together, it is suggested that T cells in the peripheral blood, especially Th2-type cells, of asthmatic patients migrate from blood into bronchial tissue without inflammatory stimulation by a mechanism other than chemokines such as MDC and TARC and their ligands of CCR4.…”
Section: Discussionmentioning
confidence: 99%